Characterization of natal and neonatal teeth: A literature review - Salguero-Astudillo, Mariana (2023)
Natal and neonatal teeth are considered a relatively rare congenital anomaly in which teeth erupt prematurely at the time of birth or within the first 30 days of life. The worldwide prevalence of this condition ranges from one in every 1,000 live births to one in every 3,000 live births. In Colombia, there are no defined prevalence and incidence rates. The exact etiology of natal and neonatal teeth remains unknown, and it is considered to have a multifactorial origin. However, the current main theory is based on the superficial positioning of the dental germ together with other factors that can accelerate tooth eruption. The finding of natal and neonatal teeth can be accompanied by the presence of Riga-Fede disease, which is considered a complication of this congenital anomaly.